Balanced scorecard for implementing united territorial communities’ social responsibility - Nadia Pylypiv; Iryna Piatnychuk; Oleksandr Halachenko; Yuliia Maksymiv; Nazariy Popadynets (Problems and Perspectives in Management, 2020)
Under decentralization, local governments gain more rights and opportunities to use various types of resources, thus, increasing their level of responsibility (including social responsibility) for the use of resources. The paper aims to reveal the consequences of decentralization reform for the indicators of united territorial communities (UTCs) budgeting that reflect their general socio-economic condition, as well as the nature of the latter one; to adapt the balanced scorecard (BSC) to the feature of UTCs’ functioning, and to develop the UTCs strategic map. The paper indicates that the system of balanced indicators is an analytical tool for ensuring the realization of the concept of social responsibility of the UТСs. The research resulted in the development of the balanced scorecard of indicators for UTCs. It includes the following blocks: internal business processes, funding, service providers, service consumers, and environment. The research contributed to the development of UTCs strategic map based on BSC adapted to the peculiarities of UTCs. The strategic map provides an opportunity to link strategic goals of UTCs with the developed BSC blocks and allows for a successful implementation of the concept of UTCs’ social responsibility in conditions of the need to achieve sustainable development.